The relationship between undernutrition and humoral immune status in children with pneumonia in Papual New Guinea - Cripps, A.; Otczyk, D.; Barker, J.; Lehmann, Deborah; Alpers, Michael Philip (Medical Society of Papua New Guinea, 2008)
Malnutrition is a significant risk factor for childhood infectious diseases in developing countries, including Papua New Guinea (PNG). Whilst the mechanisms are not fully understood there is little doubt that impairment of immune function is a major contributing factor in enhancing disease susceptibility in malnourished children. This susceptibility has been clearly shown for pneumonia in PNG. The aim of this study was to examine the effect of undernutrition on the humoral immune profile in children less than 60 months of age with pneumonia. The study was cross-sectional with measurements of nutritional status and parameters of the immune response being assessed simultaneously. The children were grouped according to age for the purpose of comparative analysis. The children were from the Goroka region of the Eastern Highlands Province of PNG and had been admitted to hospital with moderate-severe pneumonia. They were classified as undernourished (less than 80% weight for age) or nourished (greater than or equal to 80% weight for age). Serum albumin, IgG, IgA and IgM and salivary albumin and IgA were measured. Antibodies to nontypeable Haemophilus influenzae outer membrane protein and Escherichia coli O antigen were also determined in serum and saliva. Undernourished children aged less than 49 months had lower levels of serum albumin than nourished children throughout this age range. Lower values of salivary IgA were observed in infants (less than 13 months of age) than in older children, with a larger proportion of younger children having no detectable IgA.The age-related immunological profile was similar in undernourished and nourished children. At different age intervals the concentration of immunoglobulins in serum and saliva from undernourished children was generally found to be less than or the same as that from nourished children. In most cases undernourished children had lower levels of specific antibodies than nourished children but for some antibodies in some age groups the levels in the undernourished were higher. In conclusion, undernutrition was associated with hypoalbuminaemia and reduced humoral immune responses in children with pneumonia but its immunological effects varied with age in an unpredictable way.